Possible H-Mode Transition with Vertically Placed Limiters - Ohkawa, Tihiro (Kakuyūgō kenkyū, 1987)
The possibility of producing the H-mode in the limiter discharge of tokamaks is discussed. Except for the large magnetic shear of divertor configurations, the limiters placed vertically appear to mimic the diverted configuration.